IL-1 and IL-1ra are key regulators of the inflammatory response to RNA vaccines - Tahtinen, Siri; Tong, Ann-Jay; Himmels, Patricia; Oh, Jaehak; Paler-Martinez, Andres; Kim, Leesun; Wichner, Sara; Oei, Yoko; McCarron, Mark J; Freund, Emily C; Amir, Zhainib Adel; de la Cruz, Cecile C; et al. (Nature immunology, 2022)
The use of lipid-formulated RNA vaccines for cancer or COVID-19 is associated with dose-limiting systemic inflammatory responses in humans that were not predicted from preclinical studies. Here, we show that the 'interleukin 1 (IL-1)-interleukin 1 receptor antagonist (IL-1ra)' axis regulates vaccine-mediated systemic inflammation in a host-specific manner. In human immune cells, RNA vaccines induce production of IL-1 cytokines, predominantly IL-1β, which is dependent on both the RNA and lipid formulation. IL-1 in turn triggers the induction of the broad spectrum of pro-inflammatory cytokines (including IL-6). Unlike humans, murine leukocytes respond to RNA vaccines by upregulating anti-inflammatory IL-1ra relative to IL-1 (predominantly IL-1α), protecting mice from cytokine-mediated toxicities at >1,000-fold higher vaccine doses. Thus, the IL-1 pathway plays a key role in triggering RNA vaccine-associated innate signaling, an effect that was unexpectedly amplified by certain lipids used in vaccine formulations incorporating N1-methyl-pseudouridine-modified RNA to reduce activation of Toll-like receptor signaling.